The situations and strategies of amyloid⁃β⁃directed passive immunotherapy for Alzheimer's disease - Ya LI; An⁃ni ZHANG; Xu⁃ling WU; Yan ZHAO; Gang CAI; Dian HE (Chinese Journal of Contemporary Neurology and Neurosurgery, 2019)
It is widely believed that amyloid β⁃protein (Aβ) plays a core role in the pathogenesis of Alzheimer's disease (AD). Thus A β is one of main targets in the therapeutic explorations for AD. Currently, clearance of A β by passive immunotherapy is an important strategy for the treatment of AD. However, no consistent conclusions have been obtained from various clinical trails. We summarize the current situations of A β⁃directed passive immunotherapy for AD, and speculate that the failure of A β⁃directed passive immunotherapy for AD may be related to the intrinsic characteristics of A β⁃IgG glycosylation. Therefore, modifications of N ⁃ glycosylation on the Fc domain of A β⁃IgG and using a sequential administration mode of proinflammation⁃antiinflammation may be an effective strategy for passive immunotherapy for AD. DOI：10.3969/j.issn.1672⁃6731.2019.12.014